Aerobic Versus Resistance Training Effects on Ventricular-Arterial Coupling and Vascular Function in the STRRIDE-AT/RT Trial - Lekavich, Carolyn L.; Allen, Jason D.; Bensimhon, Daniel R.; Bateman, Lori A.; Slentz, Cris A.; Samsa, Gregory P.; Kenjale, Aarti A.; Duscha, Brian D.; Douglas, Pamela S.; Kraus, William E. (Frontiers in Cardiovascular Medicine, 2021)
Background. The goal was studying the differential effects of aerobic training (AT) versus resistance training (RT) on cardiac and peripheral arterial capacity on cardiopulmonary (CP) and peripheral vascular (PV) function in sedentary adults. Methods. In a prospective randomized controlled trial, we studied the effects of six months of AT versus RT in 21 subjects. Testing included cardiac and vascular ultrasoundography and serial CP for ventricular-arterial coupling (Ees/Ea), strain-based variables, brachial artery flow-mediated dilation (BAFMD), and peak VO2 (pVO2; mL/kg/min) and peak O2-pulse (O2p; mL/beat). Results. Within AT (n=11), pVO2 of 4.23 mL/kg/min (SD 0.93) (p=0.03); O2p of 1.80 mL/beat (SD 0.003) (p<0.01); BAFMD 0.90 (SD 0.28) (p=0.02); and BAFMD 0.93cm (SD 0.35) (p=0.04) were higher. Within RT (n=10) left ventricular end diastolic volume 7.0 mL (SD 3.08; p=0.05) was higher. Comparing AT and RT, post exercise, rVO2 2.97, (SD 1.22), (p=0.03), O2p 0.01 (SD 1.3), (p=0.01), resting average BAMD 1.06 (SD 0.03), (p=0.01), and post hyperemic peak brachial artery diameter 1.00 (SD 0.45), (p=0.05) were higher in AT, but Ees/Ea 0.68mmHg/ml (SD 0.60) p=0.03 and percentage flow-mediated dilation 3.14%, (SD 1.24) (p=0.02) were higher in RT. Discussion. The differential effects of AT and RT have important implications for exercise modality and clinical endpoints.